Preparation of Silver-Doped Silica Powder and Particles by Sol-Gel Method - Li, Y.L.; Li, F.; Wu, C.Y. (Asian Journal of Chemistry, 2011)
Silver-doped silica has attracted widely interests in science and technique fields. In this research, silver-doped silica have been synthesized via a two-step sol-gel process at room temperature, where silver nitrate has been employed as silver resource, tetraethyl orthosilicate as silicon precursors and 3-mercaptopropyltrimethoxysilane as a chelator for silver. After the sol-gel process was completed, silver ions were reduced by formaldehyde. Silver-doped silica powder, silica colloidal particles and silica/silver/silica trilayer particles have been prepared by changing the experimental conditions. The morphologies of obtained materials were observed by field emission transmission electron microscopic images and scanning electron microscopy. Energy dispersive X-ray spectroscopic analysis was used to investigate the element composition of the resulted materials and the results revealed the existence of S, Si, O, C and Ag in the obtained materials. This strategy provides a facile, low-cost and green methodology for the creation of silver doped silica materials.